Practical aspects of apixaban use in clinical practice: continuing the theme - S. N. Bel'diev (Столичная издательская компания, 2015)
Currently there are no generally accepted guidelines for the use of apixaban together with CYP3A4 and/or P-glycoprotein (P-gp) inhibitors. Analysis of clinical and pharmacological studies suggests that apixaban dose should be reduced to 2.5 mg twice daily when co-administered with a strong CYP3A4 and P-gp inhibitors, such as azole antimycotics, HIV protease inhibitors and clarithromycin. However, it is preferred to avoid apixaban combination with strong CYP3A4 and P-gp inhibitors in patients with a creatinine clearance (CrCl) <30 mL/min. According to preliminary calculations, apixaban dose should also be adjusted in patients with CrCl <70-80 ml/min, receiving less potent inhibitors of CYP3A4 and/or P-gp, such as diltiazem, naproxen, verapamil, amiodarone and quinidine.